The trichothecene neosolaniol stimulates an emetic response through neuropeptide Y2 and serotonin 3 receptors in mink - Wu, Qinghua; Guo, Dawei; Jia, Hui; Nepovimova, Eugenie; Wu, Wenda; Kuca, Kamil (Toxicology, 2021)
Type A trichothecene neosolaniol (NEO) is considered a potential risk to human and animal health by the European Food Safety Authority (EFSA). To date, available data do not allow making conclusions about the toxicological properties of this toxin. Trichothecenes have been previously demonstrated to induce emetic responses in mink, and this response has been associated with neurotransmitter peptide YY (PYY) and serotonin (5-hydroxytryptamine, 5-HT). The goal of this study was to compare emetic effects of NEO administered by intraperitoneal and oral routes and relate these effects to PYY and 5-HT. The effective doses resulting in emetic events in 50% of the animals following intraperitoneal and oral exposure to NEO were 0.4 and 0.09 mg/kg bw, respectively. This emetic response corresponded to elevated PYY and 5-HT levels. Blocking the neuropeptide Y2 receptor diminished emesis induction by PYY and NEO. The 5-HT3 receptor inhibitor granisetron completely restrained the induction of emesis by 5-HT and NEO. To summarize, our findings demonstrate that PYY and 5-HT play important roles in the NEO-induced emetic response.
Keywords: Receptors, Serotonin, 5-HT3; Animals; vztah mezi dávkou a účinkem léčiva; Female; receptory serotoninové 5-HT3; Receptors, Neuropeptide Y; ženské pohlaví; norek; antagonisté serotoninových receptorů 5-HT3; Vomiting; Mink; Serotonin 5-HT3 Receptor Antagonists; receptory neuropeptidu Y; zvracení; Trichothecenes; Dose-Response Relationship, Drug; trichotheceny; emetika; zvířata; Emetics